On a metric topology on the set of bivariate means - Raïssouli Mustapha; Chergui Mohamed (Acta Universitatis Sapientiae: Mathematica, 2022)
In this paper, we define a distance d on the set ℳ of bivariate means. We show that (ℳ, d) is a bounded complete metric space which is not compact. Other algebraic and topological properties of (ℳ, d) are investigated as well.